2006
DOI: 10.1098/rspa.2006.1756
|View full text |Cite
|
Sign up to set email alerts
|

Field statistics in nonlinear composites. I. Theory

Abstract: This work presents a means for extracting the statistics of the local fields in nonlinear composites from the effective potential of suitably perturbed composites. The idea is to introduce a parameter in the local potentials, generally a tensor, such that differentiation of the corresponding effective potential with respect to the parameter yields the volume average of the desired quantity. In particular, this provides a generalization to the nonlinear case of well-known formulas in the context of linear compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 15 publications
0
76
0
Order By: Relevance
“…In this connection, it is relevant to recall that field statistics in the problem at hand may be expediently formulated in terms of the total elastic energy of suitably perturbed problems. More specifically, for the case of interest here, it is not difficult to show (see, e.g., Proposition 3.2 in [43] for an analogous proof) that…”
Section: Current Porosity Fmentioning
confidence: 96%
“…In this connection, it is relevant to recall that field statistics in the problem at hand may be expediently formulated in terms of the total elastic energy of suitably perturbed problems. More specifically, for the case of interest here, it is not difficult to show (see, e.g., Proposition 3.2 in [43] for an analogous proof) that…”
Section: Current Porosity Fmentioning
confidence: 96%
“…For the special case of plane-strain loading conditions, ω N = 0 and expression (43) reduces to an earlier result of deBotton [16].…”
Section: Incompressible Constituentsmentioning
confidence: 89%
“…An equation for the single value of deformation gradient F (2) in the fiber phase can be obtained following a procedure proposed by Idiart and Ponte Castañeda [43] in the context of small-strain elasticity nonlinear. This procedure exploits the identity…”
Section: Local Fieldsmentioning
confidence: 99%
“…In addition, following arguments given in [24], it can be shown that estimates for the corresponding phase and interface averages of the plastic strain are given by expressions (37)-(38) evaluated at the optimal polarizations.…”
Section: Linear Bounds and Estimates For Periodic Compositesmentioning
confidence: 99%
“…In addition to estimating the effective response, it is of interest to estimate the statistics of the plastic strain field. Following arguments given in [24], it can be shown that the nonlinear estimates for the average plastic strain in each phase and on each set of interfaces are given by the corresponding averages in the LCC (see below).…”
Section: 21mentioning
confidence: 99%